Natural gas - Wan Abu Bakar, Wan Azelee (Sciyo, 2010)
This chapter contains a description of background of natural gas: what exactly natural has is?, how it is formed and how it is found in nature, history of natural gas: a brief history and development of modern natural gas; resources, how much abundance, where to find and what is the composition of natural gas; Uses: application and the important of energy source; natural gas versus environment: emission from the combustion of natural gas; natural gas technology: role of technology in the evolution of the natural gas industry; Purification of crude natural gas: various technologies used to convert sour to sweet natural gas; synthesis of artificial natural gas: methanation reaction.